Pengaruh Disiplin Kerja, Pengalaman Kerja Dan Lingkungan Kerja Terhadap Kinerja Guru Pada SMP Negeri 10 Kota Bima - Fatihatul Jannah; I Made Suardana; Baiq Ertin Helmida (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2023)
This study aims to see the effect of work discipline, work experience, and work environment on teacher performance at SMP Negeri 10 Kota Bima. So that the variables in this study consist of 3 (three) independent variables, namely work discipline (X1), work experience (X2), work environment (X3) and 1 (one) performance dependent variable (Y). the sample in this study were 40 teachers. The sampling technique uses Probability Sampling with the Simple Random type. The data analysis technique used is multiple linear regression analysis using the SPSS program. Based on the results of the multiple linear regression test, namely Y = 11,021+0.222X1+0.351X2+0.075X3. The results of this study also show that based on the t test the work experience variable partially has a significant effect with the results of the tcount value of 2,883 on performance. Based on the t test, it can be seen that the work experience variable has a more dominant influence on performance with a value of 2,883. The results of this study also show that based on the F test (simultaneous) the work discipline, work experience and work environment variables have a joint effect on the performance variable with a value of 8,249.